2006
DOI: 10.1016/j.ydbio.2006.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Conserved and acquired features of adult neurogenesis in the zebrafish telencephalon

Abstract: Our understanding of the cellular and molecular mechanisms underlying the adult neural stem cell state remains fragmentary. To provide new models on this issue, we searched for stem cells in the adult brain of the zebrafish. Using BrdU tracing and immunodetection of cell-type-specific markers, we demonstrate that the adult zebrafish telencephalon contains self-renewing progenitors, which show features of adult mammalian neural stem cells but distribute along the entire dorso-ventral extent of the telencephalic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

52
502
1
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 384 publications
(564 citation statements)
references
References 86 publications
52
502
1
5
Order By: Relevance
“…Transgenic lines failed in some instances to faithfully reproduce the expression pattern of the endogenous gene in adult animals even though they do so at embryonic stages (Blader et al, 2003;Adolf et al, 2006). Hence, we compared expression of Tg(olig2:EGFP) with endogenous olig2 mRNA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Transgenic lines failed in some instances to faithfully reproduce the expression pattern of the endogenous gene in adult animals even though they do so at embryonic stages (Blader et al, 2003;Adolf et al, 2006). Hence, we compared expression of Tg(olig2:EGFP) with endogenous olig2 mRNA.…”
Section: Resultsmentioning
confidence: 99%
“…In situ hybridization on vibratome brain slices (50 mm thickness) was performed as described in Adolf et al (2006). Fluorescent in situ hybridization and probe synthesis for olig2 and sox10 was performed as described in Lam et al (2009).…”
Section: In Situ Hybridizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, they are progenitor cells ultimately capable of generating all brain cell types during mammalian embryogenesis before disappearing in adults (Gotz and Barde, 2005;Bonfanti and Peretto, 2007;Noctor et al, 2007;Malatesta et al, 2008). In other vertebrates, including teleost fish, radial cells persit in adult (Onteniente et al, 1983;Menuet et al, 2003Menuet et al, , 2005Zupanc and Clint, 2003;Pellegrini et al, 2007) and it was recently shown that radial cell can generate neurons throughout adult life in fish Adolf et al, 2006). The role of aromatase in radial glial cells is poorly understood, but estrogens are now strongly suspected to participate in the process of embryonic, adult or reparative neurogenesis (Garacia-Segura et al, 2001;Martinez-Cerdeno et al, 2006;Galea, 2008;Mouriec et al, 2008;Barha et al, 2009;De Nicola et al, 2009;Kimmel et al, 1995).…”
Section: Introductionmentioning
confidence: 99%